Loss of INK4a/Arf gene enhances ultraviolet radiation‐induced cutaneous tumor development. Issue 11 (9th July 2017) - Ahmad, Israr; Guroji, Purushotham; DeBrot, Amanda H.; Manapragada, Padma P.; Katiyar, Santosh K.; Elmets, Craig A.; Yusuf, Nabiha
Abstract: The CDKN2A locus encodes for tumor suppressor genes p16 INK4a and p14 Arf which are frequently inactivated in human skin tumors. The purpose of this study was to determine the relationship between loss of INK4a/Arf activity and inflammation in the development of ultraviolet (UV) radiation‐induced skin tumors. Panels of INK4a/Arf ‐/− mice and wild‐type (WT) mice were treated with a single dose of UVB (200 mJ/cm 2 ). For long‐term studies, these mice were irradiated with UVB (200 mJ/cm 2 ) three times weekly for 30 weeks. At the end of the experiment, tissues were harvested from mice and assayed for inflammatory biomarkers and cytokines. A single dose of UVB resulted in a significant increase in reactive oxygen species (ROS) and 8‐dihydroxyguanosine (8‐oxo‐dG) lesions in INK4a/Arf −/− mice compared to WT mice. When subjected to chronic UVB, we found that 100% of INK4a/Arf −/‐ mice had tumors, whereas there were no tumors in WT controls after 24 weeks of UVB exposure. The increase in tumor development correlated with a significant increase in nuclear factor (NF)‐κB, cyclooxygenase‐2 (COX‐2), prostaglandin E2 (PGE2 ) and its receptors both in UVB‐exposed skin and in the tumors. A significant increase was seen in inflammatory cytokines in skin samples of INK4a/Arf ‐/‐ mice following treatment with chronic UVB radiation. Furthermore, significantly more CD11b + Gr1 + myeloid cells were present in UVB‐exposed INK4a/Arf ‐/‐ mice compared to WT mice. Our data indicate that by targeting UVB‐induced inflammation, it may be possible to prevent UVB‐induced skin tumors in individuals that carry CDKN2A mutation.